Sosialisasi dan Peningkatan Kapasitas Perangkat Nagari Dalam Penyusunan Dokumen Pelaksanaan Anggaran (DPA) dan Rancangan Anggaran Kas (RAK) Sesuai Dengan Permendagri No. 20/2018 tentang Pengelolaan Keuangan Desa - Suryaningsih Suryaningsih; Rianda Prima Putri; Zamhasari Zamhasari; Tengku Fahrul Gafar (Universitas Kristen Indonesia Toraja, 2023)
The village government is required to carry out village financial management in a transparent, accountable, participatory, orderly and disciplined manner. Therefore, after the APBDesa has been determined, the village head assigns village officials as executors of village financial management (PPKD) to prepare Budget Implementation Documents (DPA). This DPA consists of; Village Activities and Budget Plans (RKA), Village Activity Work Plans (RKK), and Budget Plans (RAB). This community service is carried out so that the nagari apparatus has the capacity to compile these three documents. The steps taken in this service activity are: site visits, site analysis, socialization, FGD, and closed with the practice of preparing DPA. The result of this community service activity is that the nagari apparatus understands more about regulations in village financial management, knows the flow in preparing DPA and RAK, and becomes skilled in preparing DPA and RAK.